Column Bioleaching of Fluoride-Containing Secondary Copper Sulfide Ores: Experiments With Sulfobacillus thermosulfidooxidans - Rodrigues, Michael L. M.; Santos, Guilherme H. A.; Leôncio, Hamilton C.; Leão, Versiane A. (Frontiers in Bioengineering and Biotechnology, 2019)
Bioleaching is a mature technology, which is widely employed commercially in the leaching of primary sources of metals (ores, concentrates and mine residues). The current work discussed the effects of aluminium sulphate additions to the growth medium, PLS recirculation and bleeding on the column bioleaching of secondary copper sulphide ores with a significant content of fluoride-containing minerals. Fluoride is toxic to bacteria at the pH of bioleaching but its toxicity may be overcome in the presence of soluble aluminium and ferric iron. Therefore, experiments were carried out in 10 cm x 100 cm height aerated columns, loaded with 10 kg of crushed and agglomerated copper ore and inoculated with Sulfobacillus thermosulfidooxidans. Initially, fluoride concentrations of up to 2.5 g/L in the pregnant leach solution were observed due to the fast dissolution of fluoride-bearing minerals. Aluminium was added to the leaching solution to reduce the Al/F ratio so that the concentration of HF (the main toxic species) was decreased, but while the total fluoride concentration was higher than that of aluminium, the bacterial population as low. Therefore the current work emphasizes that it is possible to set up conditions to enable bioleaching even at high fluoride concentrations. Following this approach, copper extractions above 90% were achieved for a H2SO4 consumption ranging from 128.8 Kg/tonne to 206.1 Kg/tonne.